The major facilitator superfamily transporter Knq1p modulates boron homeostasis in Kluyveromyces lactis - Svrbicka, Alexandra; Toth Hervay, Nora; Gbelska, Yvetta (Folia microbiologica, 2016)
Boron is an essential micronutrient for living cells, yet its excess causes toxicity. To date, the mechanisms of boron toxicity are poorly understood. Recently, the ScATR1 gene has been identified encoding the main boron efflux pump in Saccharomyces cerevisiae. In this study, we analyzed the ScATR1 ortholog in Kluyveromyces lactis--the KNQ1 gene, to understand whether it participates in boron stress tolerance. We found that the KNQ1 gene, encoding a permease belonging to the major facilitator superfamily, is required for K. lactis boron tolerance. Deletion of the KNQ1 gene led to boron sensitivity and its overexpression increased K. lactis boron tolerance. The KNQ1 expression was induced by boron and the intracellular boron concentration was controlled by Knq1p. The KNQ1 promoter contains two putative binding motifs for the AP-1-like transcription factor KlYap1p playing a central role in oxidative stress defense. Our results indicate that the induction of the KNQ1 expression requires the presence of KlYap1p and that Knq1p like its ortholog ScAtr1p in S. cerevisiae functions as a boron efflux pump providing boron resistance in K. lactis.
Keywords: regulace genové exprese u hub; homeostáza; fungální proteiny; membránové transportní proteiny; Kluyveromyces; Saccharomyces cerevisiae; promotorové oblasti (genetika); Fungal Proteins; Homeostasis; Membrane Transport Proteins; Boron; bor; Gene Expression Regulation, Fungal; Promoter Regions, Genetic